The Effect Of Household Consumption Expenditure (PKRT) And Gross Fixed Capital Formation (PMTB) On Economic Growth (PDRB) In East Java For The Period 2012 To 2021 - Miftahul Istifadah; Andriani (International Journal of Religion and Social Community, 2023)
This research is based on two growth theories, namely the Neoclassical which says that one of the factors of economic growth is influenced by the amount of spending that interacts with each other in an area and the Harrod-Domar theory/Keynes development theory which says that the most important factor of economic growth is capital formation (investment). Knowing the value of a region's economic growth can be seen from the Gross Regional Domestic Product (GRDP/PDRB ) data. The constituent elements include Household Consumption Expenditure (HCE/PKRT) and Gross Fixed Capital Formation (GFCF/PMTB) which represent investment value. In this case, the researcher intends to test whether the influence of the independent variables consisting of PKRT and PMTB has an effect on the dependent variable, namely economic growth (GRDP/PDRB ) of East Java Province. The approach used is quantitative with the type of associative research and analyzed using multiple linear regression methods. Using secondary data, namely GRDP/PDRB at constant prices, East Java province for the period 2012 to 2021. The results of the analysis show that both simultaneously and partially, the two variables (PKRT and PMTB) have a significant and positive effect on Economic Growth (GRDP/GRDP ) of East Java Province with an influence level of 99.2%. That is, this study supports the two theories mentioned above.